Thermoforming Machine For Produced of the Kaotan Packaging - Sugtakchan, Konthee; Wilakham, Don; Intawong, Naret (Frontiers in Engineering Innovation Research, 2019)
This research aims to design and produce a small thermoforming machine. The working principle of the machine was to continuously feed a 0.3 millimeter thick polyethylene terephthalate sheet into the mold position. The polyethylene terephthalate sheet was heated by infrared heater at a temperature range of 240 oC to 260 oC until softened. Then the softened sheet was pulled by vacuuming force inside the mold. Finally it was fed to the cutting unit to achieve the desired container shape for Kaotan packaging. The Kaotan packaging was designed to have a suitable compartment for the Kaotan product size and to prevent damage from side impact during transportation. Manufacturers could also be able to put their own logos or trade marks on the kaotan packages. Results showed that the constructed thermoforming machine was able to mold the kaotan packaging container according to purpose of the design. The suitable producing condition for thermoforming machine was optimum production temperature of 260 oC. The preheating time (PT) and Vacuum forming time (VFT) were 20 seconds and 5 seconds, respectively. The vacuum pressure used in forming was 0.005 bar. Analysis of thickness of kaotan packaging revealed that the container was thickest at the center and tended to get continuously thinner towards the edge of the kaotan packaging. Production capacity of the thermoforming machine was 704 pieces per day. The economic analysis showed that the cost of producing kaotan packaging with thermoforming machines was 2.14 baht per piece, with a return of investment within a period of 2 years and 2 months.